Respuesta :
The simplest form of the given expression is 3 x squared y (RootIndex 4 StartRoot y EndRoot)
How to solve equation?
4√81x^8 y^5
= (81x^8 y^5)1/4
= 81x^8×1/4 × y^5×1/4
= 81x² × y^5/4
= 3x²y × 4√y
Therefore, the be expression RootIndex 4 StartRoot 81 x Superscript 8 Baseline y Superscript 5 Baseline EndRoot is equivalent to 3 x squared y (RootIndex 4 StartRoot y EndRoot.
Learn more about equation:
https://brainly.com/question/18760518
Answer:
B on Edge2020
Step-by-step explanation:
Used a calculator and took the unit test.